2003
DOI: 10.1046/j.1463-1318.2003.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Anal sphincter tears in patients with rectal prolapse and faecal incontinence

Abstract: Anal sphincter tears are common in patients presenting with rectal prolapse and faecal incontinence. The faecal incontinence associated with prolapse appears to be multifactorial in aetiology. Anal sphincter defects are likely to contribute to persistent faecal incontinence or recurrence following rectal prolapse. Endoanal ultrasound derived knowledge of anal sphincter injury may guide surgical management in problematic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In this case, as in about 80% of known cases [1], the patient had full-thickness rectal prolapse with co-existing fecal incontinence, that is, involuntary excretion of fecal material at inappropriate moments or places recurring more than twice a month [2]. We attributed this problem to the pudenda - nerve damage seen on the external sphincter EMG.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this case, as in about 80% of known cases [1], the patient had full-thickness rectal prolapse with co-existing fecal incontinence, that is, involuntary excretion of fecal material at inappropriate moments or places recurring more than twice a month [2]. We attributed this problem to the pudenda - nerve damage seen on the external sphincter EMG.…”
Section: Discussionmentioning
confidence: 78%
“…More than 80% of patients with full-thickness rectal prolapse have co-existing fecal incontinence [1]. The physiopathology of this condition remains partly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies showed anal sphincter lesions using imaging procedures or anal asymmetry using physiology. 11,12 In the former study, both internal and external sphincter defects were observed in 71 percent of patients with full-thickness rectal prolapse. This group does not seem to be representative of the population study, because data were retrospectively collected in only 21 patients during a seven-year period.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the etiologic factors of sphincter defects are not discussed. 11 In the second study, a nonconsecutive series of 44 patients who suffered from incontinence were studied and the degree of rectal intussusception has been taken into account. Interestingly, 74 percent of the population study had a surgical past history of the perineum and 43 percent showed sphincter defect revealed by endosonography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation